Analisis Hak dan Kewajiban Warga Negara dalam Bidang Pendidikan Sebagai Pondasi Keadilan Sosial - Diva Rianita Putri Surinjaya; Jea Afiva; Sri Suparmi (Journal of Legal, Political, and Humanistic Inquiry, 2025)
This study highlights the interrelationship between the right to education and the obligation to support its provision as a fundamental basis of social justice. Article 31 of the 1945 Constitution of the Republic of Indonesia guarantees the right to education while simultaneously stipulating the obligation to undertake basic education and assigning the state responsibility to provide adequate educational services. The study aims to analyze how the implementation of these rights and obligations influences the equitable distribution of access, the quality of education, and the realization of social justice, with a particular focus on three dimensions: the legal framework, inhibiting factors, and the impact of implementation on social justice. The methodology employed is a literature review of eleven scholarly articles published between 2020 and 2025. The findings indicate that inequalities in access to education persist due to geographical constraints, economic disparities, inadequate infrastructure, uneven teacher distribution, and low levels of public awareness. Government initiatives through inclusive policies and the Indonesia Smart Program have not yet achieved optimal effectiveness. This study affirms that social justice can only be realized when the right to education is equitably accessible, supported by the concerted efforts of government, communities, educational institutions, and learners. Inclusive, equitable, and high-quality education constitutes the principal foundation for a just society.